The Quantum Compass Mechanism in Cryptochromes (Communications in Computational Chemistry, 2025)
Cryptochrome flavoproteins are prime candidates for mediating magnetic sensing in migratory animals via the radical pair mechanism (RPM), a spin-dependent process initiated by photoinduced electron transfer. The canonical FAD – tryptophan radical pair exhibits pronounced anisotropic hyperfine couplings, enabling sensitivity to geomagnetic fields. However, maintaining spin coherence under physiological conditions and explaining responses to weak radiofrequency fields remain unresolved challenges. Alternative radicals, such as superoxide $({\rm O}_2^{•−})$ and ascorbate $({\rm Asc}^{•−}),$ have been proposed to enhance anisotropy or suppress decoherence. This review summarizes the quantum basis of magnetoreception, evaluates both canonical and alternative radical pair models, and discusses amplification strategies including triads, spin scavenging, and bystander radicals. Emphasis is placed on how molecular geometry, exchange and dipolar interactions, and hyperfine topology modulate magnetic sensitivity. Key open questions and future directions are outlined, highlighting the need for structural and dynamical data under physiological conditions.
Keywords: radical pair mechanism; Cryptochrome; spin dynamics; magnetoreception